2004
DOI: 10.1139/e04-011
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphy and tectono-sedimentary evolution of the Late Ordovician to Middle Devonian Gaspé Belt in northern New Brunswick: evidence from the Restigouche area

Abstract: The Gaspé Belt in the Restigouche area comprises three successions separated by a Late Silurian (Salinic) disconformity and an Early Devonian angular unconformity. The lower, Upper Ordovician to Lower Silurian sequence consists of siliciclastic turbidites of the Boland Brook and Whites Brook formations (Grog Brook Group), overlain by calcareous turbidites of the Pabos and White Head formations (Matapédia Group), and slope and shelf deposits of the Upsalquitch and Limestone Point formations (lower Chaleurs Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
94
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 54 publications
5
94
0
Order By: Relevance
“…Spores and acritarchs (Wilson et al 2004), as well as brachiopods from the Indian Point Formation in Gaspé, Quebec (Bourque and Lachambre 1980), indicate a Pridolian to middle Lockhovian age. Wilson et al (2004) reported a U-Pb (zircon) age of 415.0 ± 0.5 Ma for the Squaw Cap Felsite, which intrudes the Indian Point Formation. Terminology used for the crinoid endoskeleton follows Moore et al (1978) and Ubaghs (1978a).…”
Section: Locality and Horizionmentioning
confidence: 99%
See 3 more Smart Citations
“…Spores and acritarchs (Wilson et al 2004), as well as brachiopods from the Indian Point Formation in Gaspé, Quebec (Bourque and Lachambre 1980), indicate a Pridolian to middle Lockhovian age. Wilson et al (2004) reported a U-Pb (zircon) age of 415.0 ± 0.5 Ma for the Squaw Cap Felsite, which intrudes the Indian Point Formation. Terminology used for the crinoid endoskeleton follows Moore et al (1978) and Ubaghs (1978a).…”
Section: Locality and Horizionmentioning
confidence: 99%
“…The Indian Point Formation consists mainly of moderately to strongly calcareous mudstone, fine-grained sandstone and wackestone, and commonly contains fossils of stromatoporoids, brachiopods, trilobites, crinoids and rugose corals (Wilson et al 2004). Spores and acritarchs (Wilson et al 2004), as well as brachiopods from the Indian Point Formation in Gaspé, Quebec (Bourque and Lachambre 1980), indicate a Pridolian to middle Lockhovian age.…”
Section: Locality and Horizionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Campbellton Formation overlies the Val d' Amour Formation rhyolite dated at 407.4 ± 0.8 Ma (Wilson et al 2004). Miospores in the Campbellton Formation place it in the Emphanisporites annulatus-Camarozonotriletes sextantii Assemblage Zone which corresponds approximately to the Polygnathus dehiscens to Polygnathus serotinus conodont zones of early Emsian to early late Emsian age (Richardson and McGregor 1986).…”
mentioning
confidence: 99%